Lipid radicals and oxidized cholesteryl esters in low- and high-density lipoproteins in patients with β-thalassemia: Effects of iron overload and iron chelation therapy - Lerksaipheng, Pakawit; Paiboonsukwong, Kittiphong; Sanvarinda, Pimtip; Luechapudiporn, Rataya; Yamada, Ken-Ichi; Morales, Noppawan Phumala (Free radical biology & medicine, 2024)
Iron overload results in lipid peroxidation (LPO) and the oxidative modification of circulating lipoproteins, which contributes to cardiovascular complications in patients with β-thalassemia. Investigating LPO may provide opportunities for the development of novel therapeutic strategies; however, the chemical pathways underlying iron overload-induced LPO in β-thalassemia lipoproteins remain unclear. In this study, we identified various species of lipid radicals (L•), the key mediators of LPO, and oxidized cholesteryl esters (oxCE) derived from the in vitro oxidation of major core lipids, cholesteryl linoleate (CE18:2) and cholesteryl arachidonate (CE20:4); the levels of these radical products in low-density lipoproteins (LDL) and high-density lipoproteins (HDL) were measured and compared between β-thalassemia patients and healthy subjects by using a specific fluorescent probe for L• with a liquid chromatography-tandem mass spectrometric method. Our results demonstrated that iron overload substantially decreased the levels of CE18:2 and CE20:4 substrates and α-tocopherol, resulting in higher levels of full-length and short-chain truncated L• and oxCE products. In particular, CE epoxyallyl radicals (•CE-O) were observed in the lipoproteins of β-thalassemia, revealing the pathological roles of iron overload in the progression of LPO. In addition, we found that intermission for two weeks of iron chelators can increase the production of these oxidized products; therefore, suggesting the beneficial effects of iron chelators in preventing LPO progression. In conclusion, our findings partly revealed the primary chemical pathway by which the LPO of circulating lipoproteins is influenced by iron overload and affected by iron chelation therapy. Moreover, we found that •CE + O shows potential as a sensitive biomarker for monitoring LPO in individuals with β-thalassemia. [Display omitted] •Iron overload results in the production of various lipid radicals and oxidized cholesteryl esters species in lipoproteins.•Short-term intermission of iron chelators significantly increases the level of iron-dependent lipid peroxidation products.•CE epoxyallyl radicals (•CE-O) show potential as new biomarkers for monitoring lipid peroxidation in β-thalassemia.